The effectiveness of physics PTechLS module in a rural secondary school in Malaysia - Alias, Norlidah; DeWitt, Dorothy; Siraj, Saedah; Abd Rahman, Mohd Nazri; Gelamdin, Rashidah Begum; Abd Rauf, Rose Amnah (2015)
The PTechLS module combines learning styles with the use of technology to increase students’ learning experience, especially in learning abstract concepts. The PTechLS module prototype was developed by Norlidah Alias (2010). The aim of this study is to evaluate the effectiveness of the implementation of the Physics PTechLS module in a rural secondary school in Malaysia. The PTechLS module was implemented from year 2012 to year 2014. The study adopted the exploratory implementation design which incorporates a quasi-experimental research design. 15 students agreed to participate in this study. In addition, a retrospective usability evaluation of the the implementation of thePTechLS module, with two Physics teachers as the users was conducted. The findings of this study showed that there were significant difference in the pre-test and post-test scores. This indicates that students’ achievement score could improve after using the Physics PTechLS module. The interview with the teachers showed that the Physics PTechLS module could be used as a resource. In addition, further improvements of the PTechLS module were suggested. Hence, there is possibility that the Physics PtechLS Module could be used in other secondary schools in rural areas in Malaysia to improve students’ achievement and interest in Physics.